TEACHING AND LEARNING SYSTEM OF EQUATIONS IN TWO VARIABLES IN COOPERATIVE LEARNING WITH (STUDENT TEAMS ACHIEVEMENT DIVISION) STAD TYPE - Glory Indira Diana Purba (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2015)
The purpose of this study are: describe the achievement levels of mathematical problem-solving abilities of students taught with cooperative learning strategies oriented type STAD in system of equations in two variables subject; describe the activity levels of students taught with cooperative learning STAD-oriented type of problem.This research was conducted experimental studies in State Junior High School 2 Lubuk Pakam. The selection of samples used as the experimental group and control group carried out at random (random sampling). Variables in this research is the application of cooperative learning-oriented type STAD whereas the dependent variable (dependent variable) is a mathematical problem-solving abilities of students.The data in this study were analyzed using descriptive statistical analysis and inferential analysis. Descriptive analysis intended to describe the results of students' problem-solving skills, student activities, and student response to learning. Key words: Equation of Two Variables, Cooperative Learning